Atenuação do estresse por alta temperatura durante o estádio reprodutivo do feijoeiro-comum, em função da inoculação de Bacillus subtilis - Lima, Bruna Coelho de (2020)
The present work aimed to evaluate the effect of high temperature in common bean genotypes during the reproductive stage due to the inoculation of plants with Bacillus subtilis. The study was conducted in a plant growth chamber. The experimental design used was in randomized blocks containing three treatments, two cultivars and six replications. The treatments were established by inoculation of two strains of B. subtilis and the control. The cultivars used were: IAC Imperador and TAA Dama. Rhizobacteria was inoculated directly on each seed, at a dosage of 0.1 ml with 109 cells per ml of B. subtilis AP-3 or AP-12. The plants received periodic moisture replacement and were subjected to thermal stress when reaching the reproductive stage with an increase in temperature to 28 ° / 33 ° C. The duration of the stress period was ten days. The duration of the experiment was 55 days. Biometric, flowering, biochemical, microbiological and spectral analyzes were performed on beans. The inoculation of B. subtilis was efficient to increase bacterial colonization in the rhizosphere and to promote the growth of common bean IAC Imperador submitted to the condition of thermal stress in the reproductive period. There was a reduction in the abortion of flowers and an increase in the number of pods in the cultivar IAC Imperador submitted to thermal stress due to inoculation with B. subtilis. After the period of thermal stress the plants inoculated with B.s. (AP-3) showed higher concentrations of proline and peroxidase activity in the leaves. During the period of thermal stress, plants inoculated with B. subtilis showed higher concentrations of leaf ethylene. The inoculation of common bean with the B. subtilis strain AP-3 also reduced the thermal stress evaluated by the higher reflectance in the red edge region in the spectral analysis.